Respectful maternity care in midwifery professionalism: experiences of mothers with gestational diabetes mellitus - Juanda Syafitasari; Rismayani Rismayani (Universitas Aisyiyah Yogyakarta, 2026)
Gestational Diabetes Mellitus (GDM) requires comprehensive and respectful maternity care to improve maternal health outcomes. Midwifery professionalism plays an important role in ensuring quality care through the principles of Respectful Maternity Care (RMC). This study aimed to explore the experiences of midwives and pregnant women with GDM regarding the implementation of professional midwifery care. A qualitative study with a phenomenological approach was conducted from March to April 2025 at Sukamerindu Health Center. Data were collected through in-depth interviews with seven participants, consisting of three midwives, three pregnant women with GDM, and one health center head selected using purposive sampling. Data were analyzed using Braun and Clarke’s thematic analysis. The findings identified four major themes: (1) continuous and responsive care as a form of professional responsibility, (2) emotional support and a sense of security in midwife–patient relationships, (3) patient-centered and non-discriminatory care, and (4) system support and equitable access to health services. Midwives demonstrated professionalism through continuity of care, effective communication, and collaboration with other healthcare providers. Emotional and spiritual support helped reduce anxiety among pregnant women with GDM. Respect for cultural values and patient involvement in decision-making strengthened trust and adherence to care. In addition, health insurance and accessible services supported care delivery, although limitations in nutritional services were still identified. In conclusion, professionalism in midwifery care for women with GDM includes clinical competence, empathy, cultural sensitivity, and system support. A holistic and patient-centered approach is needed to improve maternal care quality and patient experiences in high-risk pregnancies.